2021
DOI: 10.1017/erm.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

The immunology and immunotherapy for COVID-19

Abstract: The ongoing global pandemic of coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and significantly impacts the world economy and daily life. Symptoms of COVID-19 range from asymptomatic to fever, dyspnoea, acute respiratory distress and multiple organ failure. Critical cases often occur in the elderly and patients with pre-existing conditions. By binding to the angiotensin-converting enzyme 2 receptor, SARS-CoV-2 can enter and replicate in the host ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 130 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…It comprises two types of ligands, IL-1α and IL-1β, of which IL-1β plays a major role with systemic effects. Higher levels of IL-1β are associated with the severity of COVID-19 infection in critically ill patients [63]. Two inhibitors of the IL-1 pathway have been adopted in rheumatologic diseases: anakinra, a recombinant IL-1 receptor antagonist, which is effectively used to treat autoinflammatory diseases, and canakinumab, which is a human monoclonal antibody-neutralizing IL-1β [64].…”
Section: Therapy: Targeting the Modulation Of Cytokine Stormmentioning
confidence: 99%
See 1 more Smart Citation
“…It comprises two types of ligands, IL-1α and IL-1β, of which IL-1β plays a major role with systemic effects. Higher levels of IL-1β are associated with the severity of COVID-19 infection in critically ill patients [63]. Two inhibitors of the IL-1 pathway have been adopted in rheumatologic diseases: anakinra, a recombinant IL-1 receptor antagonist, which is effectively used to treat autoinflammatory diseases, and canakinumab, which is a human monoclonal antibody-neutralizing IL-1β [64].…”
Section: Therapy: Targeting the Modulation Of Cytokine Stormmentioning
confidence: 99%
“…IFN-based therapy: During a viral infection, the interaction between the viral genetic material and the immune system results in the activation of numerous downstream cascade responses, including the production of IFN-stimulating genes and IFN type 1, which can directly inhibit viral replication, as well as activate the cell-mediated response against the virus [63]. For these reasons, the possibility of administering exogenous IFN type 1 has been considered to assist the endogenous response to viral infection and allow more rapid clearance of the virus.…”
Section: Therapy: Targeting the Modulation Of Cytokine Stormmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic, the emergence of new strains of SARS-CoV-2 and the lack of a specific treatment for COVID-19 are drawing attention to the search for effective immunotherapy due to the possibility of increasing immunity to the virus and reducing hyperinflammation [4]. It has been shown that the immunological phenotype of COVID-19 is characterized by an increased number of neutrophilic granulocytes (NG) and depletion of lymphocytes, the ratio of NG to lymphocytes correlates with the severity of the disease and respiratory symptoms, being a predictor of an unfavorable outcome [7,10].…”
Section: Introductionmentioning
confidence: 99%